If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -2) = 8 + -3 + -1x Reorder the terms: -2(-2 + x) = 8 + -3 + -1x (-2 * -2 + x * -2) = 8 + -3 + -1x (4 + -2x) = 8 + -3 + -1x Combine like terms: 8 + -3 = 5 4 + -2x = 5 + -1x Solving 4 + -2x = 5 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 4 + -2x + x = 5 + -1x + x Combine like terms: -2x + x = -1x 4 + -1x = 5 + -1x + x Combine like terms: -1x + x = 0 4 + -1x = 5 + 0 4 + -1x = 5 Add '-4' to each side of the equation. 4 + -4 + -1x = 5 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 5 + -4 -1x = 5 + -4 Combine like terms: 5 + -4 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1
| 9y=22 | | f=(f+12)+(f+60) | | 2x^2-500x=40000 | | 64a=9*320 | | 110=39.02+.25x | | 64*3=a*320 | | 10y+6=6+10y | | -3x-7=25 | | .03(x)+.09(y)-750=14000 | | 64*a=3*320 | | x^2-80x+400=0 | | 63+-x=2x+3 | | JOSE+JOSE= | | 7y+7=7y+8 | | 3+65x=39x+9 | | a=(.5x+1)x^2+8x+12 | | .03(x)-.09(y)=14000 | | 5(2c-3)=7 | | a^2+2abi-b^2=8+6i | | 6x-1=15x-26 | | 11z=-33+8z | | 4t=2t-10 | | C=a+8 | | y=3x^4-6x^2+3 | | =31/2*(1-3)^4 | | 12.31+0.07x=12.81+0.08x | | X+8=4X+3+229 | | x/12-3=5/24 | | -12X+14=-24 | | (-5+3i)(4+7i)= | | 39+-12w=7+-16w | | 180-i=(i-56) |